Systematics and Diversity of Annelids - Capa, Maria; Hutchings, Pat (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this Special Issue, we address the state of the art of the systematics of the main annelid groups and the improvements in the diversity they hold, with special emphasis on the latest discoveries in well-studied areas, expeditions to unsurveyed areas or environments, or the use of novel techniques that allow for the improvement of biodiversity knowledge. We are hoping that this Special Issue will provide a platform facilitating a review of current knowledge on the subject, identifying current research problems, as well as indicating directions and research trends for the future.